Frequency of Blood-Brain Barrier Disruption Post-Endovascular Therapy and Multiple Thrombectomy Passes in Acute Ischemic Stroke Patients. Issue 8 (August 2019) - Luby, Marie; Hsia, Amie W.; Nadareishvili, Zurab; Cullison, Kaylie; Pednekar, Noorie; Adil, Malik Muhammad; Latour, Lawrence L.
Abstract : Background and Purpose—: The high prevalence of hyperintense acute reperfusion marker (HARM) seen after endovascular therapy is suggestive of blood-brain barrier disruption and hemorrhage risk and may be attributable to multiple thrombectomy passes needed to achieve recanalization. Methods—: Patients with acute stroke were included if they were screened from January 2015 through February 2019, received an acute ischemic stroke diagnosis involving the anterior circulation, treated with or without IV tPA (intravenous tissue-type plasminogen activator), consented to the NINDS Natural History Study, and imaged with a baseline magnetic resonance imaging before receiving endovascular therapy. Consensus image reads for HARM and hemorrhagic transformation were performed. Good clinical outcome was defined as 0–2 using the latest available modified Rankin Scale score. Results—: Eighty patients met all study criteria and were included in the analyses. Median age was 65 years, 64% female, 51% black/African American, median admit National Institutes of Health Stroke Scale=19, 56% treated with IV tPA, and 84% achieved Thrombolysis in Cerebral Infarction score of 2b/3. Multiple-pass patients had significantly higher rates of severe HARM at 24 hours (67% versus 29%; P =0.001), any hemorrhagic transformation (60% versus 36%; P =0.04) and poor clinical outcome (67% versus 36%; P =0.008). Only age (odds ratio, 1.1; 95% CI, 1.01–1.12; P =0.022) and severe HARM at 24 hours post-endovascular therapy were significantly associated with multiple passes (odds ratio, 7.2; 95% CI, 1.93–26.92; P =0.003). Conclusions—: In this exploratory study, multiple thrombectomy passes are independently associated with a significant increase in blood-brain barrier disruption detected at 24 hours. Patients with HARM post-endovascular therapy had a >7-fold increase in the odds of having multiple- versus single-pass thrombectomy. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00009243.